Public Administration Challenges in Human Resource Management in the Education Sector - Bambang Irawan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Education is one of the key aspects in a country's social and economic development. Quality and efficient education plays an important role in producing competent human resources that contribute positively to society and the economy. The purpose of this study is to analyse the challenges of public administration in human resource management in the education sector. This research employs a qualitative methodology in the form of a literature review, which implies that it will research and explain data by utilising information and textual content from various sources. The results of the study show that public administration challenges in human resource management in the education sector are complex and multifaceted issues. Budget constraints, legal complexities, changing demographics, technological developments, demands for transparency, shortages of qualified human resources and changes in teachers' working patterns all affect the quality and efficiency of education. These challenges require a holistic approach and innovative solutions to maintain and improve the quality of education